Juridical Analysis Of The Rights Of Adopted Children To The Inheritance Of A Husband And Wife Couple Who Have No Descendants Based On Islamic Inheritance Law And Ruling In Case Number 233/Pdt.P/2021/Pa.Msa - Paramita, Indah (Universitas Islam Malang, 2025)
Abstract: The family has the most important role in human life as a social creature and is a small community group, consisting of a father, mother and children. However, not all wishes are fulfilled, because sometimes there are families who do not have family members, whether due to health reasons or because it has not been granted by the Almighty, so that an adopted child is adopted (adoption). This research has 2 (two) problem formulations, namely (1) What can be classified as inheritance and who gets inheritance from married couples who have no children? (2) How is inheritance distributed to adopted children whose adoptive parents do not abandon the child according to Islamic inheritance and the decision in case Number 233/Pdt.P/2021/PA.Msa? The type of research used in this research is normative research. This research uses a statutory approach and a conceptual approach. The results of research on the rights of adopted children to inherit from a husband and wife who have no offspring based on Islamic inheritance law and Decision Number 233/Pdt.P/2021/PA.Msa. As for inheritance issues, adopted children do not inherit but are only entitled to receive 1/3 of their adoptive parents' assets.